The Effect of Ladder Drill Training on Agility Stepping Age Learn to Train Taekwondo Sports - Rifdah Nashiroh Gunawan; Nida'ul Hidayah (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of ladder drill training on stepping agility in learn-to-train taekwondo athletes. Agility training is very important in taekwondo because technical movements such as attacks and dodges require the ability to change direction and high speed of movement. This study used an experimental method with a one-group pretest-posttest design, involving 12 taekwondo athletes aged 9–12 years from Dojang Dozen, Cimahi City. The instrument used was a validated taekwondo agility test. The treatment in the form of a ladder drill training program was given 16 times for 5 weeks, with movement variations such as 2 shifts in and out, 2 switches in and out, in and out 2 sifts sideways, hop forward back and switch. After the ladder drill treatment and posttest, the posttest data was obtained with a good category agility value (agile movement) is 26.85 and the less agile category agility is 29.20, and the average pretest percentage is 28.88 and the average posttest percentage is 28.15, with an increase between the pretest and posttest of 2.5%. The results of the paired sample test showed that there was a significant increase in the post-test score compared to the pre-test, with a significance value of 0.000 (2-tailed) < 0.05. These findings prove that ladder drill is effective in improving stepping agility in young athletes, and can be used as an alternative training method in taekwondo coaching programs.